(untitled) (Discourse of Law and Administration, 2026)
Ubuntu is an African philosophy firmly ingrained in the African culture of looking out for one another. Pegging its principles on the interconnectedness of the African society, it presupposes situations where the well-being of people is subject to how everyone respects and looks out for each other in the spirit of African brotherhood. It also implies equal treatment devoid of any discrimination, thus providing protection of rights innately available to everyone as contemplated by the web of human rights instruments. Indeed, as Desmond Tutu once theorised, a person with ubuntu belongs to a greater whole, which whole gets diminished when some people within it are discriminated, oppressed or treated as if they are less human. It is therefore expected that the brotherhood and Africanness theorised under ubuntu should be extended to everyone, including LGBTQ+ persons. Applying the doctrinal legal research methodology, the paper examines the extent to which the ubuntu philosophy is applied to LGBTQ+ persons in Kenya. Legislation and judicial decisions are analysed to demonstrate the extent of uneven application of the philosophy. The paper posits that as an African country priding itself in inclusivity and oneness through ubuntu, Kenya is guilty of constitutional exclusion and legislative criminalization of LGBTQ+ persons. Even though in the recent past Kenya appears to be subtly extending the ubuntu spirit through judicial decisions, LGBTQ+ persons still remain branded ‘unnatural’, ‘abnormal’ and ‘un-African’ leading to social obliteration for being non-conformant with what is ‘natural’. Their existence remains constitutionally excluded and legislatively criminalised. The paper evaluates the usefulness of ubuntuism to the human rights situation of LGBTQ+ persons in Kenya. It is driven by the hypothesis that there exists unequal application of the philosophy resulting in systematic exclusion of LGBTQ+ persons, against the philosophy’s tenets. Specific interventions for wholistic application of the philosophy are proposed.